PEMBENTUKAN KARAKTER ANAK MELALUI PENDIDIKAN ISLAM DALAM KELUARGA - Afandi, Afif; Amirudin, Noor (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2025)
Islam provides guidance to humans, especially parents, to shape and develop their children's religious character from birth into the world. In an effort to form Islamic character, it is given to children starting from the time they are born until they reach adulthood. The aim of this research is to describe how children's character is formed through Islamic education in the family in Simbatan Village, Sarirejo District, Lamongan Regency and the supporting and inhibiting factors in forming the child's character. To achieve the research objectives, researchers used a descriptive qualitative method approach with data collection techniques used, namely observation, interviews and documentation. After that, the collected data is analyzed using the stages of data reduction, data presentation, and verification or drawing conclusions. The results of this research are the formation of children's character through Islamic education in families in Simbatan Village, Sarirejo District, Lamongan Regency, that as parents, both of them have served in accordance with their obligations, namely guiding, caring for, nurturing and educating their children with Islamic religious values. However, there are some who are not good, and need to be coached and supervised by them, due to environmental influence factors such as their peers. The supporting factors in forming a child's character are factors within the child, namely the willingness to encourage himself to practice his own religious values. Meanwhile, the inhibiting factors are the child's lack of self-awareness, time problems, and laziness.